Pruritus Features in Children with End-Stage Renal Disease Underwent Dialysis: A Cross-Sectional Study - Mehryar Mehrkash; Seyed-javad Golestaneh; Yahya Madihi; Fatemeh Paknazar; Mahdi Hadian; Mojtaba Akbari; Bahareh Abtahi-Naeini (International Journal of Pediatrics)
Objective. Evaluation of the pruritus features in children with end-stage renal disease (ESRD) who underwent dialysis at an academic tertiary pediatric dialysis center. Methods. This cross-sectional study was conducted at an academic tertiary pediatric dialysis center, Isfahan, Iran. The reviewed medical records of the children included their characteristics, dialysis properties, and laboratory parameters. The 4-item itch questionnaire was utilized to assess distribution, severity, frequency, and associated sleeping disorders. Results. Thirty ESRD patients with pruritus, including 23 males (76.7%) with a mean age of 11.7±3.64 years, were recruited. The most common cause of CKD was nephronophthisis (23.3%). The median total score of pruritus was 5 (range: 3-15). The distribution score of pruritus was directly correlated with the age (Spearman’s rho=0.42, P=0.02) and serum level of parathyroid hormone (PTH) (Spearman’s rho=0.42, P=0.04). In the reduced multiple logistic regression model, the increasing level of serum calcium was associated with increased odds of having total pruritus score≥5 (OR (odds ratio): 4.5; 95% CI 1.12 to 18.05). In addition, an increase in age for one year was found to be associated with 50% higher odds of having total pruritus score≥5 (OR: 1.5; 95% CI 1.03 to 2.18). Conclusion. Increased level of serum Ca and higher age were associated with increased odds of having more severe pruritus score in children.